Identification of biobutanol-associated genes and pathway limitations in non-virulent Bacillus anthracis 3B1 through functional genome analysis and fermentation optimization - Chan, Rosamond; Rossiana, Nia; Prismantoro, Dedat; Ozturk, Abdullah Bilal; Chua, Kah-Ooi; Suhaimi, Nurul Shamsinah Mohd; Wan-Mohtar, Wan Abd Al Qadr Imad; Doni, Febri (ELSEVIER, 2026)
Biobutanol is a promising biofuel alternative that addresses the energy crisis and reduces the environmental impact of fossil fuels. This study investigates the metabolic potential of Bacillus anthracis 3B1, isolated from rice cultivated under the system of rice intensification (SRI). As a facultative anaerobe, Bacillus anthracis 3B1 may offer greater metabolic flexibility and higher tolerance to butanol compared to strictly anaerobic Clostridium. Further gene annotation revealed that the genome of B. anthracis 3B1 lacks virulence genes such as pag, cya, and lef, indicating that the strain is non-virulent. The study integrates descriptive, exploratory, and experimental approaches by combining whole genome sequencing with the screening of various fermentation factors to optimize biobutanol yields and fermentation efficiency, supporting its application in sustainable bioenergy solutions. Functional genome analysis revealed key genes and enzymes involved in butanol biosynthesis. Annotation using the Rapid Annotations using Subsystems Technology (RAST) platform identified a butanol biosynthesis subsystem. Further functional annotation through Clusters of Orthologous Groups (COG), Gene Ontology (GO), and the Kyoto Encyclopedia of Genes and Genomes (KEGG) via eggNOG-mapper indicated the presence of genes encoding butanol-related enzymes, although KEGG analysis suggested an incomplete pathway. Despite these genomic indicators, no butanol was detected under the tested fermentation conditions. However, the strain produced metabolites such as propanol, ethanol, acetoin, carbon dioxide, and acetic acid. Fermentation experiments showed up to 72.57 % glucose consumption and a 0.5 pH drop, indicating active metabolism. These findings suggest that optimizing fermentation or metabolic engineering may be needed to realize B. anthracis 3B1 butanol potential.
Keywords: Bacillus; Biobutanol; Biofuel; Fermentation; Functional genome analysis; CLOSTRIDIUM-ACETOBUTYLICUM; BUTANOL PRODUCTION; LOCAL ISOLATE; BUTYRIC-ACID; PH; SACCHAROPERBUTYLACETONICUM; BEIJERINCKII; FUTURE; STRAIN; Biotechnology & Applied Microbiology; Engineering; Environmental Sciences & Ecology